Konstruksi Wacana Kesehatan dalam Iklan IQOS Indonesia di Channel YouTube IQOS Indonesia - Hayiz Historia Adhi Pratama (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2023)
IQOS is claimed by the company as a better solution than continuing to smoke. As a new innovation in Indonesia, Philip Morris needs to communicate this product to be known by the public. One of the methods employed by the company is advertising the product through YouTube. IQOS extensively constructs health issues in their brand advertisements. Therefore, the aim of this research is to describe the construction of health discourse in advertisements IQOS Indonesia on the IQOS Indonesia YouTube channel. This research uses a qualitative approach with a  Critical Discourse Analysis method by Norman Fairclough. The research findings indicate that the brand community and brand believers play a significant role in constructing health discourse. The constructed health discourse includes IQOS as a solution for cleanliness, IQOS as an expression of self-love and care for others, IQOS is safer for women to use, and IQOS as a solution to a problem. The contribution of this study found that advertisements on YouTube channel IQOS Indonesia reinforce the health discourse that has been claimed by the company so far